Synthesis and Characterisation of Micronutrient Based Copper Alginate and Ferric Alginate Beads for Agricultural Applications - Joyal, Mohanambal; Perumal, Andal; Mariyappillai, Anbarasu (Asian Journal of Chemistry, 2026)
The excessive use of chemical fertilizers has caused major environmental issues, emphasizing the need for sustainable nutrient delivery systems. In this work, copper and ferric alginate beads were synthesised using the ionotropic gelation method and analysed through UV-DRS, FTIR, FE-SEM, TGA, DSC and AAS techniques. The results showed that Cu2+ and Fe3+ ions had been successfully added. The copper beads had porous surfaces and the ferric beads had solid structures. Thermal studies showed that the material was more stable and AAS measured the metal contents at 18.2% Cu and 14.6% Fe. Pot experiments on black gram (Vigna mungo L.) showed that ferric alginate beads significant improved plant height (26.5 cm), pod number (32) and seed yield (6.82 g) compared to copper beads. Ferric beads also helped the roots grow better (8.8 cm, 0.75 g dry weight). Based on studies, ferric alginate beads demonstrate strong potential as eco-friendly slow-release fertilizers, while copper alginate beads provide comparatively moderate performance in supporting nutrient release.